2013
DOI: 10.1002/qj.2196
|View full text |Cite
|
Sign up to set email alerts
|

Selective ensemble‐mean technique for tropical cyclone track forecast by using ensemble prediction systems

Abstract: This article proposes a selective ensemble-mean technique for tropical cyclone (TC) track forecast based on the errors of ensemble prediction system (EPS) members at short lead times (SLTs, 12 h in this study). The means (SEAV) and weighted means (SEWE) of selected EPS members are applied to EPS products from the European Centre for Medium-range Weather Forecasts (ECMWF), Japan Meteorological Agency (JMA), National Centers for Environmental Prediction (NCEP), and China Meteorological Administration for 35 TCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
7

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 29 publications
1
50
0
7
Order By: Relevance
“…The SEAV method used in this article is a selective ensemble-mean technique for TC track prediction proposed by Qi et al in 2014. It uses short lead time (SLT) position errors from every ensemble member to compose an ensemble mean for a long lead time (LLT) track forecast with a basic premise that members with smaller SLT errors are likelier to yield more accurate forecasts at LLT. The specific operational procedures are shown by the following steps ( Figure 1): (i) Due to data communication and computational requirements, EPS products often reach forecasters with a 'delay time' which is more than 6 h in operational work.…”
Section: Seav Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…The SEAV method used in this article is a selective ensemble-mean technique for TC track prediction proposed by Qi et al in 2014. It uses short lead time (SLT) position errors from every ensemble member to compose an ensemble mean for a long lead time (LLT) track forecast with a basic premise that members with smaller SLT errors are likelier to yield more accurate forecasts at LLT. The specific operational procedures are shown by the following steps ( Figure 1): (i) Due to data communication and computational requirements, EPS products often reach forecasters with a 'delay time' which is more than 6 h in operational work.…”
Section: Seav Methodologymentioning
confidence: 99%
“…Additionally, the method produced better results for a multi‐model ensemble than for a single‐model ensemble. Qi et al () proposed a selective ensemble‐mean technique for TC track forecasting from the European Centre for Medium‐range Weather Forecasts (ECMWF), Japan Meteorological Agency (JMA), US National Centers for Environmental Prediction (NCEP) and China Meteorological Administration (CMA) for 35 TCs in the WNP from 2010 to 2011. The results showed that the means of selected EPS members (SEAV) for the JMA EPS was the most skilful of the tested methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EA can be a means to reduce errors further (Mackey and Krishnamurti, 2001;Qi et al, 2014). To test the EA effect on the TAR prediction, the TARs were averaged at each station by sequentially increasing the number of ensemble members from the typhoon of a higher track similarity, and they were then compared with the observations.…”
Section: Effects Of Track Similarity Ensemble Averaging (Ea) and Imentioning
confidence: 99%
“…Advanced and new techniques are constantly emerging in predicting TC tracks. For example, Qi et al (2014) proposed a selective ensemble mean technique for TC track forecast based on the errors of ensemble prediction system members at short lead times. Similarly, a method of retrieving optimum information of typhoon tracks in a multi-model ensemble of forecasts is explored by Tien et al (2012).…”
Section: Introductionmentioning
confidence: 99%